Modulation of Radiation-Induced Disturbances of Antioxidant Defense Systems by Ginsan - Han, Youngsoo (Oxford University Press, 2005)
There are numerous studies to indicate that irradiation induces reactive oxygen species (ROS), which play an important causative role in radiation damage of the cell. We evaluated the effects of ginsan, a polysaccharide fraction extracted from Panax ginseng, on the γ-radiation induced alterations of some antioxidant systems in the spleen of Balb/c mice. On the 5th day after sublethal whole-body irradiation, homogenized spleen tissues of the irradiated mice expressed only marginally increased mRNA levels of Mn-SOD (superoxide dimutase) in contrast to Cu/Zn-SOD, however, catalase mRNA was decreased by ∼50% of the control. In vivo treatment of non-irradiated mice with ginsan (100 mg kg(−1), intraperitoneal administration) had no significant effect, except for glutathione peroxidase (GPx) mRNA, which increased to 144% from the control. However, the combination of irradiation with ginsan effectively increased the SODs and GPx transcription as well as their protein expressions and enzyme activities. In addition, the expression of heme oxygenase-1 and non-protein thiol induced by irradiation was normalized by the treatment of ginsan. Evidence indicated that transforming growth factor-β and other important cytokines such as IL-1, TNF and IFN-γ might be involved in evoking the antioxidant enzymes. Therefore, we propose that the modulation of antioxidant enzymes by ginsan was partly responsible for protecting the animal from radiation, and could be applied as a therapeutic remedy for various ROS-related diseases.